DYNAMICS OF SOCIO-ECONOMIC CHANGES IN COASTAL FISHING COMMUNITIES IN PENAGAN VILLAGE, BANGKA REGENCY - Ahmad Nazriansyah; Basofi Sudirman; Febri Ruandi (Jurnal Syntax Transformation, 2023)
Unconventional mining (IT) practices are not foreign to the people of Bangka Belitung, including in Penagan Village. IT practices which are also carried out at sea certainly have an effect on the coastal fishing communities in Penagan Village. The dominant change is seen in the social and economic dynamics of the Penagan Village community. Social dynamics can be subdivided into aspects of education, health, and government policy. Meanwhile, economic dynamics can be further grouped into aspects of capital, access to and use of fishing technology, fishermen's income, and fishermen's lifestyle. In this study, we found IT to have a number of positive and negative impacts. However, the negative impact turned out to be more dominating for the coastal fishing community of Penagan Village.